(untitled) (Contemporary Mathematics, 2024)
This paper analyzes the stakeholders of the new energy vehicle industry strategic choices in market competition using Nash equilibrium and cooperative game theory from game theory, employing mathematical models. First, This paper constructs a game model containing multiple competitors to determine the optimal strategy of the industry in the non-cooperative situation. Secondly, the cooperative game theory is introduced to analyze the distribution of various stakeholders in the new energy vehicle industry under the condition of cooperation, and to discuss how to achieve win-win results through cooperation.Verifying the model’s effectiveness through empirical analysis, we suggest competitive strategies to be employed in the tripartite game. Our research demonstrates that game theory can provide a scientific basis for the new energy vehicle industry to devise effective competitive tactics in the intricate market environment.